DIAGNOSTIC ASSESSMENT IN DIFFERENTIATED LEARNING: SUPPORTING STUDENTS' NEEDS FOR ENHANCED LEARNING - Siti Nazilah, Amy; Ferdianto, Ferry (Cirebon International Conference on Education and Economics Proceeding, 2024)
Differentiated learning is at the forefront of efforts to create a more equitable and inclusive education system, diagnostic assessments play a key role in understanding students' individual learning needs and designing appropriate interventions. However, the implementation of diagnostic assessments in supporting differentiated learning still has challenges. This research aims to explore effective strategies in diagnostic assessment and their impact on the learning process and student learning outcomes. This research method uses a literature review approach to investigate the role of diagnostic assessment in supporting differentiation learning, analysis of key findings related to the role of diagnostic assessment in supporting differentiation learning. This includes identifying effective strategies in implementing diagnostic assessments, as well as their impact on improving learning for students. The findings show that the implementation of differentiated learning by utilizing diagnostic assessment data has a positive impact on student learning and learning outcomes. By understanding students' conditions through diagnostic assessments, teachers can determine appropriate follow-up in the form of content, process or product differentiation. The scientific contribution of this research is a deeper understanding of the role of diagnostic assessment in supporting differentiation learning.